Calculation of the protective properties against ionizing radiation of refractory cements based on alkaline compounds - Khrystych, Mykhailo (National Technical University "Kharkiv Polytechnic Institute", 2025)
The article presents a theoretical study that allows predicting the protective properties of alumina cements, namely, calculating the mass absorption coefficient for cement compositions. It has been determined that materials based on these cements can effectively withstand the simultaneous aggressive effects of various types and can be used in protective structures against radioactive radiation and elevated temperatures.
Keywords: protective properties; alumina cement; strength; mass absorption coefficient of ionizing radiation